Population pharmacokinetic model of tacrolimus in adult liver transplant recipients - Jovanović, Marija; Ćulafić, Milica; Pejić, Nina; Štulić, Miloš; Kovačević, Milena; Vezmar Kovačević, Sandra; Miljković, Branislava; Ćulafić, Djordje; Vučićević, Katarina (Archives of Pharmacy, 2022)
Tacrolimus is an immunosuppressant used to prevent graft rejection after liver transplantation. The narrow therapeutic range and great variability in pharmacokinetics indicate the need for therapy individualization. The aim of the study was to develop and validate the base pharmacokinetic model of tacrolimus using data collected during therapeutic drug monitoring. The study included 29 liver transplant recipients followed up at Clinic for Gastroenterology and Hepatology, Clinical Center of Serbia. Using the NONMEM® program, we analyzed tacrolimus concentrations (Ctrough) measured in whole blood (260). Pharmacokinetics have been described as one-compartment model with first-order absorption and elimination. Internal validation was performed using graphical assessment, bootstrap method and visual predictive check (VPC). Typical value of oral clearance (CL/F) was 30.4 L/h, while value of oral volume of distribution was 5770 L. The value of the absorption rate constant was fixed at 4.48 h-1. Interindividual variability was best described by the exponential model, and residual by the additive model. Interindividual variability for CL/F was 38.2%. Individual predicted concentrations (IPRED) showed better agreement with the measured values ​​than population predicted values ​​(PRED). Conditional weighted residuals (CWRES vs PRED, CWRES vs TIME) were mostly between -2 and +2 standard deviations. The parameters obtained by bootstrap analysis do not deviate significantly from the model. Median, 5th and 95th percentiles ​​in the VPC method mostly were within the simulated 95% confidence interval. The obtained population pharmacokinetic model, after additional optimization, can be used for individualization of the tacrolimus dosing regimen in the population of liver transplant recipients.